Feldman Fieldmouse; a fable. - Benchley, Nathaniel, 1915-1981.; Knight, Hilary (New York, Harper & Row, 1971)
A fieldmouse is visited by his uncle who teaches him to work and to take the risk of dancing in the moonlight.
Keywords: Mice -- Fiction